Match-Fixing in Korean Football: Corruption in the K-League and the Importance of Maintaining Sporting Integrity - Brooks, Graham; Lee, Ju-Lak; Kim, Hak-Kyong (International JOURNAL OF CONTENTS, 2012)
Fraud and corruption is a problem that undermines the credibility and integrity of all sport. It affects fans, owners, shareholders, officials, and players. With the recent scandal in the K-League in Korea, the importance of maintaining the integrity of Korean football is presently of great importance. While other European or Asian football leagues have been plagued with fraud and corruption, Korea has maintained its professional sporting integrity successfully until recent times. This paper is an examination as to why players in the K-League succumbed to match- fixing in 2011. Firstly, we discuss the important role of sport in Korea, which is not to be underestimated. Secondly, we briefly illustrate the range and types of fraud and corruption in international football. Thirdly, we focus on the match-fixing and gambling scandal currently engulfing the K-League. Fourthly, we make some practical suggestions on how to combat and increase resilience to fraud and corruption in football. Finally, in the conclusion, we suggest that much needs to be done to reduce the incident of fraud and corruption in football worldwide, particularly through employing a clear counter fraud strategy. KCI Citation Count: 2